2005
DOI: 10.1055/s-2005-837771
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Side Effects by Combining Clozapine with Amisulpride: Case Report and Short Review of Clozapine-Induced Hypersalivation

Abstract: Side effects from a high-dose clozapine treatment for a schizophrenic patient led to massive compliance problems. The dose of clozapine could be halved without recurrence of an acute psychotic symptomatology by concomitantly administering amisulpride. The side effects, especially hypersalivation, disappeared almost entirely, which in turn led to good compliance. In a short review we would like to present the pathophysiology and therapeutic options of clozapine-induced hypersalivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Some authors reported that clinical efficacy could be maintained after augmenting clozapine therapy with amisulpride and lowering daily doses of clozapine, thereby reducing common side-effects such as sedation, hypersalivation and weight gain (Croissant et al, 2005;Cook and Hoogenboom, 2004;Zink et al, 2004). To the best of our knowledge, the present study is the first prospective randomized double-blind, placebo-controlled cross-over study of the beneficial effects of short-term amisulpride augmentation (400 mg/day) of stable ongoing clozapine therapy in the reduction of CIH.…”
Section: Discussionmentioning
confidence: 96%
“…Some authors reported that clinical efficacy could be maintained after augmenting clozapine therapy with amisulpride and lowering daily doses of clozapine, thereby reducing common side-effects such as sedation, hypersalivation and weight gain (Croissant et al, 2005;Cook and Hoogenboom, 2004;Zink et al, 2004). To the best of our knowledge, the present study is the first prospective randomized double-blind, placebo-controlled cross-over study of the beneficial effects of short-term amisulpride augmentation (400 mg/day) of stable ongoing clozapine therapy in the reduction of CIH.…”
Section: Discussionmentioning
confidence: 96%
“…If symptoms emerge following dose reduction, supplementation with other drugs may improve antipsychotic efficacy without causing sialorrhea. In a single case study, amisulpiride added to clozapine decreased its requirement and reduced troublesome sialorrhea (Croissant et al 2005).…”
Section: Management Strategiesmentioning
confidence: 99%
“…The atypical antipsychotic amisulpride is effective in the treatment of positive, negative, and depressive symptoms of schizophrenia and has low propensity for extrapyramidal symptoms and weight gain [6,21,31,32]. Accordingly, amisulpride has been repeatedly recommended for combination with other atypical antipsychotics in treatment-resistant patients [5,20]. Pronounced prolactin elevations associated with the D2 antagonistic properties of amisulpride, especially in women [9,11,28,37], may lead to unwanted clinical symptoms [17,27,39].…”
mentioning
confidence: 99%